Pemanfaatan Instagram Sebagai Media Komunikasi Pemasaran Online dalam Meningkatkan Penjualan (Studi Kasus Instagram @Avros_Cafe) - Alimuddin, M. Gatot; Vita, Nadra Ideyani (Universitas Medan Area, 2025)
This study aims to analyze the use of Instagram as a marketing communication medium in increasing sales at Avros Cafe. Instagram, as a visual-based social media platform, has evolved into an effective marketing tool for small and medium-sized businesses. Through features such as product photos and videos, informative captions, and the use of hashtags, Instagram allows businesses to reach a wider audience at a relatively low cost. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study show that Avros Cafe makes the most of Instagram by applying the 4P theory of products, prices, places, and promotions to increase marketing effectiveness. Instagram helps Avros Cafe display products with attractive visuals, provide clear price information, introduce the café's atmosphere, and carry out relevant promotions. The use of Instagram also strengthens relationships with customers through direct interaction and more personalized communication. Thus, Instagram has proven to be effective in increasing sales and introducing the Avros Cafe brand to a wider audience.